USING ORIGAMI AS THE CONTEXT IN LEARNING SIMILARITY AT FIFTH GRADE - Khairun Nisak; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Sriwijaya University Learning and Education International Conference, 2018)
This research aimed to produce learning trajectory in learning Similarity using Origami as the context, trough Pendidikan Matematika Realistik Indonesia (PMRI) approach. The method of this research was design research that consisted of three phases namely preliminary design, design experiment (pilot experiment and teaching experiment) and retrospective analysis. The research was conducted in Sekolah Dasar Negeri 24 Palembang. Data collection was obtained by interviews, observations, video recording, collecting student work, pre-test and post-test. The results of this research showed that Learning Trajectory (LT) which contained a series of learning process using Origami could help students to find the concept of Similarity.